A Missiological Exploration of Luke 4:18 and the Challenge of Caste Discrimination in Seventh-day Adventist Churches of India - Kumar, Santosh (International review of mission, 2024)
This article expands on a prior study on caste discrimination in the Seventh-day Adventist (SDA) Church in India. Rooted in a missiological framework, it examines the transformative potential of Luke 4:18 in addressing the challenges faced by marginalized communities in the SDA context. The article draws on findings from earlier qualitative research on historical roots, missiological perspectives, and the relevance of biblical passages to inform a narrative inquiry approach on the hermeneutics of Luke 4:18. By aligning the text with complementary passages, it delves into the historical trajectory of caste discrimination within SDA churches and revisits the contemporary challenges faced by marginalized members. This article highlights the crucial roles of church leadership and educational initiatives in fostering inclusivity and combatting discrimination by integrating a hermeneutical lens into actionable strategies. Finally, it contributes to ongoing discussions on social justice and equality in religious communities, offering a nuanced perspective informed by both qualitative insights and hermeneutical exploration.